Micro and SMEs financing and credit availability: the Italian case - Nadotti, Loris (Finansowanie i dostępność kredytów sektora MŚP na przykładzie Włoch, 2012)
The problem of small and medium enterprises (SMEs) financing and credit availability is very important for the economic development of a country. The difficulty in accessing bank credit and its costs for small enterprises becomes even more interesting considering the imminent coming into force of the third version of the Basel Accord. The scope of the paper is to investigate if SMEs are still dependent on bank loans or if they are starting to raise money on capital markets. Using descriptive method and data analysis, this reflection aims to give a reading of the recent financial situation and the current relationship between actors on the Italian credit market, according to new trends in the behavior of markets and intermediaries, as well as the influences of the most recent regulatory measures
Nauki o Finansach = Financial Sciences, 2012, Nr 1 (10), s. 73-96
Keywords: credit; SME; Italian case study; bank loan